Pengaruh Bermain Peran Terhadap Perkembangan Sosial Anak Usia Dini - Yublina Sofians Maniti; Esi Debora Alokabel; Dince Mariana Bulan; Desi Agustina Bekak; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Early childhood education is an effort to develop basic abilities that are important for children from birth to the age of six as the golden age (diamond age). One aspect of development that needs to be optimized is the child's social emotional development. This research aims to determine the effect of role playing methods on the social emotional development of early childhood. This research uses a quantitative approach with an ex post facto type of research. The research subjects were 10 children aged 5-6 years at PAUD Bait'El Naimata, Kupang City, using a total sampling technique. The research instrument is a psychological scale in the form of a Likert scale for role-playing variables and children's social-emotional development.  The data analysis technique was carried out using simple linear regression analysis. The results of simple linear regression research using a simultaneous test (F test) show a significance value of 0.000 <0.05, which means that role playing has a significant effect on the social emotional development of early childhood. The coefficient of determination (R Square) value of 0.072 shows that role playing contributes 7.2% to children's social emotional development. Thus, it can be concluded that the role playing method has a positive and significant effect on the social development of early childhood and is recommended for application in PAUD learning.